What Works in Conservation: 2017 - Ockendon, Nancy; K. Smith, Rebecca; V. Dicks, Lynn; J. Sutherland, William (83982d68-aac8-4910-9134-f7cab1412a64, 2017)
"Is leaving headlands in fields unsprayed beneficial for wildlife? Is paying farmers to cover the costs of bird conservation measures effective? Is using prescribed fire beneficial for young trees in forests? Does translocating frogs benefit wild populations? Is providing artificial roost structures for bats beneficial? What Works in Conservation has been created to provide practitioners with answers to these and many other questions about practical conservation. This book provides an assessment of the effectiveness of 763 conservation interventions based on summarized scientific evidence. Chapters cover the practical global conservation of amphibians, bats, birds and forests, conservation of European farmland biodiversity and some aspects of enhancing natural pest control, enhancing soil fertility and control of freshwater invasive species. It contains key results from the summarized evidence for each conservation intervention and an assessment of the effectiveness of each by international expert panels. The accompanying website www.conservationevidence.com describes each of the studies individually, and provides full references. This is the second edition of What Works in Conservation, which is revised on an annual basis. It will also available online as a free-to-download PDF at www.conservationevidence.com"